1997
DOI: 10.1016/s0022-5347(01)64134-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Routine Semen Analysis and Critical Assessment of Sperm Morphology by Kruger Classification to Therapeutic Varicocelectomy

Abstract: Surgical correction of varicocele was associated with significant improvement in sperm morphology evaluated using Kruger classification. Concentration and count improved after varicocelectomy. Changes were observed as early as 3 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 19 publications
0
28
0
4
Order By: Relevance
“…It is widely accepted that abnormality in sperm morphology has a negative impact on fertilisation, similar to motility defects [5,13] . Although varicocele decreases the normal morphological sperm ratio, examinations performed according to standard criteria revealed no relevant specific morphology defects [14][15][16] . Various sperm morphology defects from sperms with oval or flat heads to amorphous sperm forms may be present [2,14] .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is widely accepted that abnormality in sperm morphology has a negative impact on fertilisation, similar to motility defects [5,13] . Although varicocele decreases the normal morphological sperm ratio, examinations performed according to standard criteria revealed no relevant specific morphology defects [14][15][16] . Various sperm morphology defects from sperms with oval or flat heads to amorphous sperm forms may be present [2,14] .…”
Section: Discussionmentioning
confidence: 89%
“…Vazquez-Levin et al [15] reported that sperm morphology assessed according to Kruger's classification improved considerably after varicocelectomy in 33 men. A study by Kibar et al [24] suggested that sperm head and acrosomal defects improved significantly after varicocelectomy in 90 patients with oligoasthenoteratozoospermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Відсоток позитивних ре-зультатів у лікуванні чоловічого безпліддя стабілізувався на рівні 16-32 % [14]. Така низька ефективність є наслідком того, що до теперішнього часу недостатньо вивчено при-чини чоловічої ін-та субфертильності.…”
Section: вступunclassified
“…поряд з причинами, котрі порушують репродуктивну здатність -і є складовою екскреторного безпліддя, існують причини секреторного безпліддя, серед яких запаль-ні захворювання репродуктивної системи, викликані урогенітальними інфекціями, і становлять від 8,5 до 38,4 % [14,20].…”
Section: вступunclassified